The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1111/j.1939-1676.2003.tb01327.x
|View full text |Cite
|
Sign up to set email alerts
|

Regurgitant Fraction Measured by Using the Proximal Isovelocity Surface Area Method in Dogs with Chronic Myxomatous Mitral Valve Disease

Abstract: Previous studies have demonstrated that regurgitant fraction can be measured by using the proximal isovelocity surface area (PISA) method. For this study, we utilized this Doppler echocardiographic method to estimate the magnitude of mitral regurgitation in dogs with myxomatous mitral valve disease. Seventeen older, small dogs with chronic mitral regurgitation and no to mild myocardial failure were studied. A blinded observer judged the clinical severity of mitral regurgitation to be mild, moderate, or severe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 21 publications
2
28
2
Order By: Relevance
“…In addition, one study demonstrated that the LA/Ao ratio was correlated significantly with the regurgitation fraction obtained by PISA (Gouni et al, 2007). In our study, the RF PISA showed higher values for group III (68.380% ± 16.153%) and the literature reports that values greater than 50% should be considered significant in cases of moderate to severe MR (Gouni et al, 2007), with values greater than 75% considered severe in small dogs (Kittleson and Brown, 2003 (Choi et al, 2004).…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…In addition, one study demonstrated that the LA/Ao ratio was correlated significantly with the regurgitation fraction obtained by PISA (Gouni et al, 2007). In our study, the RF PISA showed higher values for group III (68.380% ± 16.153%) and the literature reports that values greater than 50% should be considered significant in cases of moderate to severe MR (Gouni et al, 2007), with values greater than 75% considered severe in small dogs (Kittleson and Brown, 2003 (Choi et al, 2004).…”
Section: Discussionsupporting
confidence: 62%
“…This fact is reported in the literature as a result of MR worsening, leading to the onset of signs of CHF (Carlsson et al, 2009). Moreover, the severity of MR is a major determinant of LA size in small animals (Kittleson and Brown, 2003). The LA/Ao ratio was greater in group III compared with the other groups; this could be justified by the fact that this ratio is directly influenced by the increase in the left atrium.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Last, aortic stroke volume was assessed by pulsed wave Doppler trace of the aortic flow velocity by multiplying the aortic area by the velocity time integral using the left apical 5-chamber view. 23 …”
Section: Conventional Echocardiography and Doppler Examinationmentioning
confidence: 99%
“…The regurgitant stroke volume (RSV) and the effective regurgitant orifice (ERO) were estimated by the proximal isovelocity surface area (PISA) method, which estimates regurgitation volume quantitatively [4,5,11].…”
Section: Methodsmentioning
confidence: 99%